Validation of the german Inflammatory Bowel Disease Fatigue (IBD-F) questionnaire = Erster validierter deutschsprachiger Fatigue-Fragebogen für PatientInnen mit chronisch-entzündlichen Darmerkrankungen (CED) - Scholz, Karina Antonia Magdalena; Thomann, Anne K.; Teich, Niels; Baumann, Hartmut; Walldorf, Jens; Büning, Carsten; Rosania, Rosa; Canbay, Ali E.; Arnim, Ulrike von (Zeitschrift für Gastroenterologie, 2023)
Introduction Fatigue is a common symptom in patients with inflammatory bowel diseases (IBD). To date, there is no instrument to assess IBD-specific fatigue in German. The aim of this study was to translate the IBD Fatigue (IBD-F) scale and to test its psychometric properties in a German IBD population. Methods After completing the translation process, 20 IBD patients participated in a pilot testing phase. For further analyses, 180 IBD patients with fatigue answered the IBD-F (Sections I, II, III) and the IBD Questionnaire (IBDQ-D). Reliability was tested by using Cronbach's alpha and corrected item-total correlation. Exploratory factor analyses (EFA) were carried out. Spearman’s correlation was calculated between the IBD-F and IBDQ-D . 78 patients could be included to calculate the test-retest reliability. Results The German version of the IBD-F shows high face and content validity. Internal consistency was excellent, with a Cronbach's alpha of 0.93-0.98. Corrected item-total correlations ranged from 0.51 to 0.89. The correlation between the IBD-F and the IBDQ-D was statistically significant for Section I (rs=-0.59; p<0.01) and Section II (rs=-0.76; p<0.01) of the IBD-F. The EFA identified one relevant factor for each section. Test-retest reliability was acceptable for Section I (intraclass correlation coefficient (ICC)=0.73) and Section II (ICC=0.84). Conclusion The German version of the IBD-F is a reliable and valid tool to assess fatigue in IBD.
Artikel online veröffentlicht: 09. Mai 2022
Gesehen am 05.05.2023